Effects of retinoic acid excess on expression oh Hox 2.9 and Krox 20 and on morphological segmentation in the hindbrain of mouse embryos - MURPHY, PAULA (Nature Publishing Group, 1991)
Mouse embryos were exposed to maternally administered RA on day 8.0 or day 7 3/4 of development, i.e. at or just before the differentiation of the cranial neural plate, and before the start of segmentation. On day 9.0, the RA-treated embryos had a shorter preotic hindbrain than the controls and clear rhombomeric segmentation was absent. These morphological effects were correlated with alterations in the spatiotemporal distribution patterns of two genes, Hox-2.9 and Krox-20, which are expressed in the otic and preotic hindbrain and in specific neural crest cell populations. Hox-2.9 was expressed throughout the preotic hindbrain region, instead of being confined to rhombomere 4. Krox-20 was not expressed rostral to the Hox-2.9 domain, i.e. its normal rhombomere 3 domain was absent. The Hox-2.9/Krox-20 boundary was ill-defined, with patches of alternating expression of the two genes. In migrating neural crest cells, Hox-2.9 expression was both abnormally extensive and abnormally prolonged. Neural crest cells expressing Krox-20 remained close to the neural tube. Embryos exposed to RA on day 8 1/4 appeared to be morphologically normal. We suggest that early events leading to rhombomeric segmentation and rhombomere-specific gene expression are specifically vulnerable to raised RA levels, and may require RA levels lower than those in the region of somitic segmentation.
PUBLISHED
Keywords: Zoology